BILATERAL POST-TRAUMATIC DIAPHRAGMATIC HERNIAS - S. A. Plaksin; L. P. Kotel’Nikova (Вестник хирургии имени И.И. Грекова)
Traumatic diaphragmatic hernias could be clinically apparent and diagnosed after months and years after trauma. Bilateral ruptures of the diaphragm rarely appeared. Patients (46 cases) with diaphragmatic hernias were treated at the period from 1998 to 2010. The rate of diaphragmatic hernias consisted of 41,3%, bilateral post-traumatic hernias was noted in 2,2%. The article presents a follow-up study of bilateral diaphragmatic hernia, which was formed on the left (after 1 year) and on the right after 5 years. Diagnosis was supported by radiographic contrast research and computed tomography data. The stomach and omentum were displaced to the pleural cavity on the left, the transversely colon and omentum had a shift on the right. Thoracotomy and diaphragm plasty were performed in both cases. Hernial orifice was located in the area of esophageal opening and crura of diaphragm. It is necessary to increase clinical suspicion in relation to possibility of diaphragmatic hernia origin after severe closed trauma.